Application of Kalindaqdaq Values in Developing Dakwah in Kayuangin Village, Malunda Subdistrict, Majene Regency - Syamsuddin, Syamsuddin; Nasriah, St. (Jurnal Mercusuar, 2021)
This text discusses the use of Kalindaqdaq values in the development of village dakwah in Kayuangin village, Malunda district, Majene regency. Effective instruments are needed for the delivery of Islamic teachings in the process of dakwah development. The Kalindaqdaq tradition, which contains messages that are in line with religious order, dakwah messages, faith, and Shariah ethics, can be used as a means of dakwah in the Mandar community. The study aims to investigate the process of the Kalindaqdaq tradition in Kayuangin village, as well as the delivery process and dakwah messages in the Kalindaqdaq poetry to help the public, especially young people, understand the meaning of the tradition beyond mere artistic performance.